Polímeros biodegradáveis - uma solução parcial para diminuir a quantidade dos resíduos plásticos - Franchetti, Sandra Mara Martins [UNESP]; Marconato, José Carlos [UNESP] (Sociedade Brasileira de Química, 2006)
The large use of plastics has generated a waste deposit problem. Today plastic wastes represent 20% in volume of the total waste in the municipal landfills. To solve the disposal problem of plastics methods have been employed such as incineration, recycling, landfill disposal, biodegradation and the use of biodegradable polymers. Incineration of plastic wastes provokes pollution due to the production of poisonous gases. Recycling is important to reduce final costs of plastic materials, but is not enough in face of the amount of discarded plastic. In landfills plastic wastes remain undegraded for a long time, causing space and pollution problems. Biodegradation is a feasible method to treat some plastics, but intensive research is necessary to find conditions for the action of microorganisms. All of these methods are important and the practical application of each one depends on the type and amount of the plastic wastes and the environmental conditions. Therefore, a great deal of research has focused on developing biodegradable plastics and its application because it is an important way for minimizing the effect of the large volume of plastic waste discarded in the world.
Biodegradable polymers - a partial way for decreasing the amount of plastic waste
Keywords: biodegradable polymers; plastic waste; biodegradation